2021
DOI: 10.1097/htr.0000000000000682
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Social Supports in Adolescents With Persistent Postconcussion Symptoms

Abstract: Objectives: To determine whether adolescents with persistent postconcussion symptoms (PPCS) differ from healthy peers in their personality traits and social supports. Setting: Specialty Concussion Clinic and Primary Care Clinic affiliated with an academic medical center. Participants: Ninety-seven adolescents (42 with PPCS, 55 healthy peers; age: 15 ± 2 years). Design: Participants completed a web-based survey that included medical and demographic characteristics, mechanisms of concussion, 10-item Big Five Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Peer and other forms of social support have been shown to be important in facilitating recovery from pediatric concussion; children identify a need to rely on friends for support during recovery and adolescents who experience persistent PCS often report lower levels of peer support. 62,63 The adolescents in our study who reported more peer problems may not have had the same access to social supports as adolescents who reported fewer peer problems and may have therefore experienced a longer time to RTP. Peer-related problems may also be a marker for other functional difficulties that put adolescents at risk of persistent PCS.…”
Section: Discussionmentioning
confidence: 92%
“…Peer and other forms of social support have been shown to be important in facilitating recovery from pediatric concussion; children identify a need to rely on friends for support during recovery and adolescents who experience persistent PCS often report lower levels of peer support. 62,63 The adolescents in our study who reported more peer problems may not have had the same access to social supports as adolescents who reported fewer peer problems and may have therefore experienced a longer time to RTP. Peer-related problems may also be a marker for other functional difficulties that put adolescents at risk of persistent PCS.…”
Section: Discussionmentioning
confidence: 92%